Engaging Parents for Improved Schooling Outcomes of Under-8 Pupils: A Teachers’ Qualitative Perception - Iyanuoluwa Olalowo; Abiola Olarogba; Moses Amosun (Educational Challenges)
Purpose. Based on the Asuwada Theory of Sociation, an indigenous theory that stresses the importance of the interactive community cycle, this study aims to understand teachers’ views of children’s schooling in the context of the parents’ engagement pathways. Education policymakers and decision-makers need to understand how outside factors affect children's education as they grow up. This is because education is a continuous, lifelong process largely predictable by activities from when and where children are born. While it is assumed that developing a child's whole personality is the teacher's job, studies have shown that this goal can be challenging to achieve when other aspects of their education are not up to par. However, studies show that parents have not shown much effort, hence this study.